The role of a nurse in the breast cancer related fatigue management - Rzepka, Katarzyna; Nowicki, Andrzej (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Fatigue, besides pain, nausea and vomiting, is the most common problem experienced by patients treated for breast cancer. It relates to a considerable number of patients and is perceived as a state that hinders day-to-day functioning. Although the majority of patients reports fatigue, the symptom is ignored or not diagnosed by physicians. There are pharmacological means available during treatment; however, the role of medicine in neutralising fatigue has not been examined in detail yet. There are proceeding standards that decrease aggravation of the fatigue syndrome to a significant extent. Education, counselling, physical exercises, rational energy management, sleep therapy and adequate nutrition are recommended as appropriate non-pharmacological procedures in neutralising fatigue. The aim of this study was to present the standards of cancer related fatigue management and to indicate the role of a nurse in the course of the (cancer related fatigue) treatment.